Water exchange technique improves colonoscopy in patients with spinal cord injury: Results of a matched cohort study - Brechmann, Thorsten; Aach, Mirko; Schildhauer, Thomas A.; Grasmücke, Dennis (Endoscopy International Open, 2024)
Background and study aims Colonoscopies in patients with spinal cord injury (SCI) frequently remain incomplete. This study aimed to evaluate the feasibility and impact of water exchange colonoscopy (WE) in patients with SCI. Patients and methods Three matched groups, each of 31 patients (WE in SCI patients [WE-SCI]) and in the general population (WE-GP), carbon dioxide-based colonoscopy in SCI patients (CO2-SCI)) were analyzed retrospectively. Results Intubation of the cecum and the terminal ileum was achieved in every case in both WE groups. The intubations among the CO2-SCI patients succeeded in 29 cases (93.5 %, ns) and 20 cases (64.5 %, P<0.001), respectively. The cecal insertion time (23:17 ± 10:17 min vs. 22:12 ± 16:48 min) and bowel preparation during cecal insertion did not differ between WE-SCI groups. Insertion in the general population was faster (13:38 ± 07:00 min, P<.001) and cleanliness was better. Both WE-SCI groups showed significantly better cleansing results during drawback; the improvement in cleanliness was highest in the WE-SCI (based on the five-step scale 1.4 ± 0.8 vs. 0.8 ± 0.8, P = 0.001). Conclusions The WE in SCI patients is feasible and safe and has the potential to improve the quality of colonoscopies substantially.
Keywords: Quality and logistical aspects; Performance and complications; Preparation